(untitled) (Marketing Journal, 2025)
This thesis explores AI-driven demand forecasting as a strategic tool for sustainable FMCG distribution. It shows how AI enhances inventory accuracy, reduces waste, and optimizes logistics. Global best practices (Unilever, P&G) illustrate realworld applications, while the case for Uzbekistan emphasizes digital integration to align with green economy goals.